Third cranial nerve palsy caused by gummatous neurosyphilis: MR findings. - Vogl, T; Dresel, S; Lochmüller, H; Bergman, C; Reimers, C; Lissner, J (American Journal of Neuroradiology, 1993)
The clinical and MR findings in an unusual case of gummatous neurosyphilis are reported. A 44-year-old woman suffering from diplopia and right-sided headaches was admitted. Physical examination and routine laboratory parameters were normal except for a third-nerve palsy. MR images revealed a contrast-enhancing lesion of the upper brain stem and third cranial nerve. Differential diagnosis included neuroma of the third cranial nerve, as well as neurosarcoidosis and other inflammatory processes. Serologic tests and lumbar puncture revealed the presence of active syphilis. After intravenous treatment with penicillin G, follow-up MR examinations showed diminishing size of the lesion with its complete resolution within 3 months.